18. Simposium Latinoamerican of coffee world coffee economy situation and outlook - Seudieu, D.O.
Sumario (Es)
Keywords: CAFE; COMERCIO EXTERIOR; PRODUCCION; CONSUMO; PRECIOS; OFERTA Y DEMANDA; ESTABILIZACION DEL MERCADO; AMERICA LATINA; MEMORIA; SIMPOSIO